2019
DOI: 10.1089/lgbt.2019.0055
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities Among Exclusively Lesbian, Mostly Lesbian, and Bisexual Young Women

Abstract: Purpose: Health disparities have been identified between groups of diverse young sexual minority women (SMW) and heterosexual women. This approach may generate sufficient group sizes for statistical analyses but obscures important differences. Moreover, some young women may not identify as ''lesbian'' or ''bisexual'' but somewhere in between. This study examined health and sexual minority identity-specific outcomes among three groups of SMW-women who identify as ''exclusively lesbian,'' ''mostly lesbian,'' and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 57 publications
(102 reference statements)
1
10
0
Order By: Relevance
“…Health-related research on SGMW is growing slowly worldwide [31][32][33], but there is less research on Chinese SGMW. According to published data from Western countries, sexual minority women experience a higher incidence of mental health disorders, including anxiety and depression, and also generally report a worse QOL than cisgender heterosexual women (CHW) [34,35]. A recent scoping review summarizing the holistic health of homosexual and bisexual Chinese over the past 20 years showed that the academic attention given to the male population is much higher than that given to female groups (96.46% vs 1.32%, respectively) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Health-related research on SGMW is growing slowly worldwide [31][32][33], but there is less research on Chinese SGMW. According to published data from Western countries, sexual minority women experience a higher incidence of mental health disorders, including anxiety and depression, and also generally report a worse QOL than cisgender heterosexual women (CHW) [34,35]. A recent scoping review summarizing the holistic health of homosexual and bisexual Chinese over the past 20 years showed that the academic attention given to the male population is much higher than that given to female groups (96.46% vs 1.32%, respectively) [20].…”
Section: Introductionmentioning
confidence: 99%
“…These include worse perceived health quality, as well as higher prevalence of chronic conditions and sexually transmitted infections among LGBTQ+ individuals compared to their heterosexual, cisgender counterparts (Centers for Disease Control and Prevention, 2020; Dai and Hao, 2019; Elliott et al, 2015; Simoni et al, 2017; Wanta et al, 2019). Further, within the LGBTQ+ community, unique health experiences and needs exist, with additional disparities apparent between the diverse populations that make up the community (Dai and Hao, 2019; Lewis et al, 2019). Disparities in healthcare access partially explain worse health outcomes observed among LGBTQ+ individuals, fueled by a range of social and structural barriers to care (Lerner and Robles, 2017; Lisy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Even though this finding did not achieve statistical significance relative to lesbian women, the magnitude of the disparity was consistent with the study hypothesis, given that bisexual women have higher risks of substance use and have poorer physical and mental health than lesbian women. 1,12,13,[26][27][28][29] The underlying cause of these disparities is thought to be related to unique stressors that bisexual individuals face relative to other LGB groups. Specifically, bisexual orientation may be more concealable than lesbian orientation because many bisexual women have male partners.…”
Section: Discussionmentioning
confidence: 99%